Maqasid Al-Shari’ah Al-Syatibi VS. Jasser Auda: Perspektif Dinamis dan Sistemik Terhadap Kebijakan Publik di Era Globalisasi - umi zaidatul Khoeriyah; Yoiz Shofwa Shafrani; Nawangsasi Kusuma Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study explores the comparative framework between Abu Ishaq Al-Syatibi and Jasser Auda in interpreting Maqasid Al-Shari’ah within the context of public policy in the globalization era. The research aims to identify the philosophical and methodological shifts from the classical normative approach of Al-Syatibi to Auda’s dynamic systemic paradigm. Employing a descriptive qualitative method through a comparative matrix, the study analyzes six dimensions of systemic analysis-cognition, hierarchical interrelatedness, systemic integrity and totality, openness, multidimensionality, and intentionality. Data were obtained from primary and secondary sources that discuss the theoretical foundations and applications of maqasid in Islamic law and public policy. Findings show that Al-Syatibi emphasizes a conservative-normative perspective focusing on the preservation of fundamental values-religion, life, intellect, lineage, and property serving as the foundation for legal stability. Conversely, Jasser Auda promotes a holistic and adaptive interpretation of maqasid that responds to social change and global issues, highlighting human rights, justice, and sustainability. The synthesis of both paradigms provides a comprehensive and integrative framework for formulating public policies that are not only normatively grounded but also contextually responsive to modern societal needs.